Cognitive decline, dual sensory loss and the use of visual aids in elderly - A narrative review - Sourav Karmakar; Animesh Mondal; Pampa Bhowmick; Gaurav Kumar Bhardwaj (Oman Journal of Ophthalmology)
The relationships between visual acuity, contrast sensitivity, stereo acuity, and cognition varied, implying that domain-specific cognitive loss patterns exist. This review aims to learn how visual aids help patients with visual impairment and cognitive decline. The electronic searches had no language restrictions or research design filters. However, from 2016 forward, searches were restricted, and the electronic databases were last examined in 2022. There were 537 papers discovered in PubMed and 18,000 articles found in Google Scholar, of which ten articles fit the criteria. Patients who participated in the trials had an average age of 81–82 years. Patients with self-reported vision difficulties had a higher incidence of dementia. The majority were female populations. Auditory and visual loss was detected in 5.5% of dementia cases versus 4.9% of nondementia subjects. Early-stage cognitive impairment raises the chance of dementia later in the disease. Along with motor dysfunction, impairments in visual memory, verbal fluency, and executive functions, as well as increased depressive symptoms, predicted worse Parkinsonian disability, highlighting the critical role of nonmotor factors such as cognitive and visual dysfunction, as well as depression, in disability, even in the early stages of Parkinsonian disability.